Palladium-Catalyzed Silylation of Aryl Chlorides with Bulky Dialkoxydisilanes - Fukui, Keitaro; Saito, Hayate; Shimokawa, Jun; Yorimitsu, Hideki (Synlett, 2020)
Arylsilanes bearing a bulky alkoxy group on the silicon were synthesized from aryl chlorides and dialkoxydisilanes under reaction conditions utilizing SingaCycle-A3 as a palladium precatalyst and lithium benzoate in wet DMA. This report proposes the first direct and catalytic method for introducing tert-butoxy- or 1-adamantyloxysilyl groups onto various aryl moieties through the silylation reaction.
Keywords: palladium; alkoxysilane; disilane; arylsilane